Administration of intravenous iron and tranexamic acid in the management of postoperative iron deficiency anaemia following free flap reconstruction: re-audit. Issue 1 (January 2021) - McLean, A.; Lowe, D.; Rogers, S.N.
Abstract: Following free tissue transfer, intravenous iron (IVI) has a role in reducing the rates of blood transfusion and more rapidly restoring haemoglobin (Hb) levels. Anaemia has a detrimental effect on survival, postoperative complications, fatigue, and health-related quality of life, therefore early correction is recommended. The aim of this re-audit is to assess the use of IVI, of tranexamic acid intraoperatively, and of perioperative blood transfusions. A total of 148 consecutive patients who underwent ablative surgery and free flap reconstruction between May 2018 and September 2019 were audited. The median (IQR) age was 66 (59, 72) years and 36% were female. For two-thirds, surgery was for cancer located in the oral cavity and two-thirds of the free flaps were soft tissue. Tranexamic acid (TXA) was used intraoperatively for 30%, red blood cells (RBC) were transfused for 20% and 55 patients (37%) received IV iron. This compares with 4%, 26%, and 0, respectively, in the initial audit. Those having IVI were more likely (56%) to have had a composite flap, a lower postoperative haemoglobin and lower discharge Hb. The Hb between four and twelve weeks' follow up, known for 40, was a median (IQR) of 122 (104, 138). There were no adverse reactions to IV iron. Although it is straightforward to administer IVI postoperatively, this re-audit demonstrates that it can be a challenge to embed change in protocols. Through raised awareness of the benefits of IVI, lack of adverse events and clarification of selection criteria, it is hoped that rates of IVI use will increase.